The Role of the Notary Supervisory Board Against Falsification of Documents by Notaries in Making Authentic Deeds - Diva Salzabila, Kanzha (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
This study aims to analyze: 1) The role of the Notary Supervisory Council against document falsification by a notary in making an authentic deed. 2) The responsibility of the Notary who falsifies documents in the making of an authentic deed. The approach method used in discussing this research problem is a sociological juridical approach. The research specifications used are descriptive analytical research. This type of data uses primary and secondary data obtained through interviews and literature studies. The data analysis method used is qualitative. The results of the study concluded: 1) The role of the Notary Supervisory Board against falsification of documents by a notary in making a deed is the attribution of authority sourced from the Legislation. The Notary Supervisory Board's role is to conduct an examination of alleged violations of the behavior and implementation of the Notary's position and impose sanctions if proven guilty. In a lawsuit involving a Notary, the Regional Supervisory Council was tasked with receiving reports, followed by an examination by the Regional Supervisory Council, and the imposition of sanctions if found guilty by the Central Supervisory Council. 2) The responsibility of a Notary who falsifies documents in making an authentic deed is a responsibility that adheres to the principle of responsibility based on fault of liability, meaning that the Notary must be responsible if the deed he made contains an error or intentional violation by the Notary, otherwise, if the element of error or violation occurs from the parties appearing, then as long as the Notary carries out his authority according to the regulations. The Notary concerned cannot be held accountable, because the Notary only records what was conveyed by the parties to be poured into the deed. False information submitted by the parties is the responsibility of the parties.Keywords: Authentic; Deed; Notary; Supervisory.